2023
DOI: 10.3390/opt4040039
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Laser-Induced Periodic Surface Structures (LIPSS) Formation in Silicon and Their Impact on Surface-Enhanced Raman Spectroscopy (SERS)

Hardik Vaghasiya,
Paul-Tiberiu Miclea

Abstract: Laser-induced periodic surface structures (LIPSS) have gained significant attention due to their ability to modify the surface morphology of materials at the micro-nanoscale and show great promise for surface functionalization applications. In this study, we specifically investigate the formation of LIPSS in silicon substrates and explore their impact on surface-enhanced Raman spectroscopy (SERS) applications. This study reveals a stepwise progression of LIPSS formation in silicon, involving three distinct sta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 52 publications
(67 reference statements)
0
2
0
Order By: Relevance
“…The formation of laser-induced periodic surface structures is a well-known phenomenon that is observed for virtually all solid materials exposed to short laser pulses of high energy, although the complexity of the involved processes still precludes its full understanding. , Despite that, the possibility of obtaining subwavelength (and even deeply subwavelength) LIPSS drives the research for their applications, particularly in the field of photonics, e.g., for polarization conversion, as a basis for sensing platforms , and distributed feedback laser resonators . Very recently, a formation of unique class of phase change LIPSS was demonstrated in films of chalcogenide PCMs. ,,, As opposed to “conventional” LIPSS that are formed due to material reorganization or removal, LIPSS in PCM exhibit spatially modulated phase transition and thus imply the possibility of reversible control.…”
Section: Multicycle and Multilevel Phase Change Lipss On Planar Waveg...mentioning
confidence: 99%
“…The formation of laser-induced periodic surface structures is a well-known phenomenon that is observed for virtually all solid materials exposed to short laser pulses of high energy, although the complexity of the involved processes still precludes its full understanding. , Despite that, the possibility of obtaining subwavelength (and even deeply subwavelength) LIPSS drives the research for their applications, particularly in the field of photonics, e.g., for polarization conversion, as a basis for sensing platforms , and distributed feedback laser resonators . Very recently, a formation of unique class of phase change LIPSS was demonstrated in films of chalcogenide PCMs. ,,, As opposed to “conventional” LIPSS that are formed due to material reorganization or removal, LIPSS in PCM exhibit spatially modulated phase transition and thus imply the possibility of reversible control.…”
Section: Multicycle and Multilevel Phase Change Lipss On Planar Waveg...mentioning
confidence: 99%
“…The inherent characteristics of ultrashort pulse duration and ultrahigh energy of a femtosecond (fs) laser can be employed to fabricate micro/nanostructures for SERS substrates, superior to the traditional chemical growth methods in terms of high efficiency, , material flexibility, minimal thermal impact, simplicity of operation without masks, environmental friendliness, and cost savings. Laser-induced periodic surface structures (LIPSSs), , as one of the most intriguing phenomena induced by fs laser, are extremely favorable for applications of micro-optical elements, nanofluidic channels, optical data storage, etc., owing to their unique properties . Research on SERS based on fs-laser-induced LIPSSs have been preliminary reported, however, without systematical investigation on their mechanisms and further applications.…”
mentioning
confidence: 99%